Exploring association between countries' self-reported International Health Regulations core capacity and COVID-19 control outcomes - Feng-Jen Tsai; Chia-Ping Lin; Battsetseg Turbat (Journal of Global Health Reports)
# Background This study aimed to evaluate the association between countries’ self-reported International Health Regulations (IHR) capacity and their COVID-19 control outcomes.